2018
DOI: 10.1111/cen.13796
|View full text |Cite
|
Sign up to set email alerts
|

Children with MEN1 gene mutations may present first (and at a young age) with Cushing disease

Abstract: This report describes a paediatric patient population with MEN1 in whom CD was the initial manifestation, confirming a previous observation that paediatric patients with MEN1 may present first with an ACTH-producing adenoma. Therefore, germline MEN1 mutations should be sought in paediatric CD and tested for when there is a suggestive family history and/or other manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…For the patients and their parents, if available, DNA was extracted either from peripheral blood samples using the Maxwell 16 Blood DNA Purification Kit in a Maxwell 16 Instrument (Promega AS1015 and AS3050) or from saliva using the Oragene-Dx collection kit and the PrepIT-L2P DNA extraction kit (DNA Genotek OGD-500 and PT-L2P-45), according to the manufacturer's protocols. Additional studies in this cohort have been reported elsewhere (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Patients and Samplesmentioning
confidence: 83%
See 1 more Smart Citation
“…For the patients and their parents, if available, DNA was extracted either from peripheral blood samples using the Maxwell 16 Blood DNA Purification Kit in a Maxwell 16 Instrument (Promega AS1015 and AS3050) or from saliva using the Oragene-Dx collection kit and the PrepIT-L2P DNA extraction kit (DNA Genotek OGD-500 and PT-L2P-45), according to the manufacturer's protocols. Additional studies in this cohort have been reported elsewhere (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Patients and Samplesmentioning
confidence: 83%
“…The Biocruces Bizkaia Health Research Institute included 10 probands (60% females), with mean age at diagnosis of 17.9 (7.5–29.0) years and median tumor size of 17.4 ( 9 20 ) mm. The NICHD cohort included 182 patients, 56.6% ( n = 103) females and 43.4% ( n = 79) males.…”
Section: Resultsmentioning
confidence: 99%
“…Two different forms of MEN1, sporadic and familial, have been described[ 23 ]. The sporadic form presents with two of the three principal MEN1-related endocrine tumors (parathyroid adenoma, enteropancreatic tumor and pituitary tumor) within a single patient, while the familial form consists of MEN1 with at least one first-degree relative showing one of the endocrine characteristic tumors[ 24 - 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative SPECT/CT is useful in localizing parathyroid cysts in most patients, with accuracy improving to 79% if it is interpreted in combination with cervical ultrasound images [26]. Two different forms of MEN1, sporadic and familial, have been described [27]. The sporadic form presents with two of the three principal MEN1-related endocrine tumors (parathyroid adenoma, enteropancreatic tumor and pituitary tumor) within a single patient, while the familial form consists of MEN1 with at least one rst-degree relative showing one of the endocrine characteristic tumors [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%